A comparative study on the performances of layer hybrids in some selected areas of Khulna region (Bangladesh Journal of Animal Science, 2013)
A survey was conducted in Batiaghata and Dacope upazilla of Khula district during the period from August to October, 2013 to observe the socioeconomic conditions of poultry farmers, existing feeding and management practices of poultry farms and performances of 5 different layer hybrids. The commercial layer hybrids considered in present study were of 30 layer farmers selected randomly from each Upazilla to collect the information. Data were collected using a pretested questionnaire by direct interview of the farmers. Collected data were analyzed using SPSS. To observe the socioeconomic conditions, the age of selected farmers, their occupation, education level, family size, land size and annual income were considered. Mean age at first lay did not vary significantly among 5 different hybrids. Average mature weights of layer birds varied significantly (P